Green Ambidextrous Leadership and Green Employee Innovative Behavior: : Mediating Effects of Knowledge Sharing and Psychological Safety and the Moderating Role of Green IT Empowerment - Muhamad El Khandiyas; Gatot Kustyadji (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
Purpose – This study aims to investigate the influence of Green Ambidextrous Leadership (GAL) on Green Employee Innovative Behavior (GEIB). It further explores the mediating roles of psychological safety and knowledge sharing, while examining Green IT Empowerment as a critical moderating variable. Design – A quantitative approach was employed, utilizing a comprehensive model to analyze the interplay between leadership, psychology, knowledge management, and technology. Data were collected from employees in the petrochemical industry and analyzed to test the structural relationships within the proposed framework. Findings – The results demonstrate that Green Ambidextrous Leadership is a pivotal factor in driving GEIB. This influence is primarily channeled through psychological safety and knowledge sharing, with psychological safety emerging as the more potent mediator. This highlights the necessity of a safe psychological climate for fostering environmental innovation. Furthermore, Green IT Empowerment significantly moderates these relationships, acting as a strategic enabler that amplifies the impact of organizational factors on green innovation. The integrated model explains 85.6% of the variance in GEIB, confirming the relevance of combining leadership, knowledge management, and technology empowerment perspectives in an industrial context. Practical implications – Organizations should prioritize leadership development programs focused on green ambidextrous competencies and invest in Green IT infrastructure. Most importantly, management must cultivate psychological safety by transitioning from a “blame culture” to a “learning culture.” This can be achieved through no-retaliation policies for speak-up behavior and reward systems that recognize “intelligent failures” in green initiatives.